Preference for Popular and World Music: A Review of Literature. (June 2017) - Williams, Matthew
Reviews of literature on music preference may provide music educators with a variety of research on information, techniques, and methods to implement in the music classroom. Calls to widen the types of music used in curricula seem to underscore the importance of research exploring preference using music other than, and in addition to, Western art music. The present review of literature explores nonmusical factors, including external characteristics and listener characteristics, as well as musical factors contributing to decisions of musical preference related to popular and world music to aid educators in planning effective and meaningful music activities.